Individual decision on antibiotic treatment. A case for utility assessment - (:unkn) unknown (My University, 2025)
Decisions on antibiotic treatment Treatment guidelines that minimise the risk of the development of antibiotic resistance may result in less effective and/or convenient therapies for individual patients. The project aims at defining individual and society’s preferences as to acceptable risk of antibiotic resistance. Background In industrialised countries, antibiotics in humans are most commonly used for the treatment of respiratory tract infections. Guidelines for the initial treatment of community-acquired pneumonia (CAP) are either aimed at maximising efficacy and convenience in the treatment of the individual patient or they try to reduce the likelihood of the development of antibiotic resistance. The effort to preserve long-term antimicrobial efficacy may result in a less effective therapy for a given patient and thus increased morbidity, namely prolonged hospitalisation and/or increased mortality. Aim The objective of the current project is to assess the preferences of patients, health care professionals and greater society for acceptable risk of antibiotic resistance development for a given increase in mortality, morbidity and/or treatment inconvenience. Computerised interviews will be used to estimate the preferences of patients, health care professionals and representative volunteer participants from the Italian, French and German speaking parts of Switzerland. Patient’s preferences can be assessed and expressed as quantitative measures known in medical decision analysis as ‘utilities’. Patients’ utilities allow the weighting of statistical probabilities for various outcomes according to patients’ preferences for these outcomes. We are working based on the assumption that guidelines for the initial treatment of CAP can be derived that maximise total expected utilities for individuals as well as the whole population. These guidelines will not only consider immediate gains in outcomes and/or treatment convenience after individual episodes of pneumonia (curing patients today), but also take into account the emergence of antibiotic resistance and changes in treatment efficacy over time (protecting the community tomorrow). Significance The methods to be introduced and the results derived will be relevant for future health policy decisions. Estimated population preferences will provide a rational decision base for acceptance of future measures towards reducing drug resistance.